Pengaruh Metode Hafalan Terhadap Kecerdasan Kognitif Siswa Pada Mata Pelajaran Pendidikan Agama Islam (PAI) Di SMP Takhassus Al-Qur’an Wonosobo - Fiqih Rizqiyah; Robingun Suyud El Syam; Nur Farida (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Education is an activity that helps people talk about what they already know in order to broaden their understanding of life's fundamentals. The foundations or principles that guide one's life, particularly those derived from religious ideals, are crucial for governing and enhancing the system of life. Based on observations made by the author at Takhassus Al-Qur'an Middle School, it is stated that there is a lack of student focus in learning and students' abilities vary in receiving learning. However, this does not rule out the possibility that students can stimulate learning more quickly. This can be done by training students' thinking through the rote method because the more the brain gets used to it, the more it will be trained and of course it will increase students' intelligence. The level of cognitive intelligence is divided into 3, namely: level of memory and understanding, level of application, level of analysis, evaluation and creativity. By using the rote method so that the level of cognitive development is observed in memory and understanding.Based on the findings of the author's research, the following conclusions can be drawn: 1) The memorization method for teaching PAI at Takhassus Al-Qur'an Middle School is in the good category, the level of cognitive intelligence of Takhassus Al-Qur'an Middle School students is known to be in the good category and level Student memorization based on memorization scores in PAI learning subjects is in the very good category. 2) hypothesis testing based on the t value, the predetermined value of tcount > ttable, namely 2.867 > 1.69389, while based on the significance value of 0.008 < 0.05, it is concluded that the rote method variable (X) has an effect on the cognitive intelligence variable (Y). simple linear regression (11.151 + 0.363 determination is 0.215, which means it has a positive influence of 21.5% and 78.5% is influenced by other factors that are not yet known by researchers. 3) Supporting factors in the memorization method for students' cognitive intelligence at Takhassus Al-Qur'an Middle School, namely using Mr. Abdurrahman al Asy'ari's method which is practiced in the tahfidz class using a special Al-Qur'an, level of perseverance, consistency in training, environment learning, and student concentration during the learning process.